Klasifikasi Pengendalian Persediaan Bahan Baku Chemical Cigarette Paper Pada PT XYZ Dengan Metode Always Better Control (ABC) - Anisti, Tiara Nanda; Nisah, Firda Ainun; Arifin, Jauhari (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
PT XYZ is a company that produces cigarette paper, in which the manufacturing process requires chemical raw materials as a key component. As an exporter, the company must maintain continuous production, even during logistical disruptions such as road closures during the Eid al-fitr holiday. This condition requires bulk ordering of raw materials before the holiday, making proper storage essential ti preserve material quality over an extended period. This study aims to classify chemical raw materials using the ABC (Always Better Control) method, which categorizes items based on annual consumption value and warehouse movement into category A (fast moving), B (medium moving), and C (slow moving). The results show 2 materials fall into category A, 1 into category B, and 4 into category C. This classification is expected to help the company develop more efficient inventory control strategies and adaptive storage systems to meet operational demands. Keywords: ABC Method, Chemical Raw Materials, Cigarette Paper, Inventory Control